DiaDENS-Cardio potential in resistant arterial hypertension treatment - G. A. Svintsova; N. Kh. Bagmanova; Yu. V. Kotovskaya; M. V. Umnikova; Zh. D. Kobalava (Кардиоваскулярная терапия и профилактика)
Aim. To investigate a new technique of transcutaneous electroneurostimulation of reflexogenic zones by shortimpulse current (DiaDENS-Cardio) as a potential method to improve blood pressure (BP) control in patients with arterial hypertension (AH) uncontrolled by three-component therapy.Material and methods. A placebo-controlled study of DiaDENS-Cardio device included 60 AH patients, receiving regular three-component antihypertensive therapy but failing to achieve the target BP level <140/90 mm Hg. BP was self-measured (SMBP) and monitored for 24 hours (24-hour BPM).Results. Systolic BP decreased after two days of DiaDENS-Cardio therapy, as demonstrated by SMBP (123,4+5,4 vs. 144,9+7,4 mm Hg; p<0,05) and 24-hour BPM (125,8+4,9 vs. 147,1+11,7 mm Hg; p<0,05).Conclusion. DiaDENS-Cardio therapy significantly improved BP control in patients with resistant AH.